Evaluation of Growth and Yield of Four Strawberry (Fragaria ananassa) Genotypes (The Agriculturists, 2014)
A pot experiment was conducted to evaluate the growth and yield performance of four strawberry germplasms at the Horticulture Farm of Sher-e-Bangla Agricultural University, Dhaka during October 2010 to April 2011. The experimental materials were four strawberry germplasms: V1 (SAU Line-01), V2 (SAU Line-02), V3 (SAU Line-03) and V4 (SAU Line-04). The experiment was laid out in a Completely Randomized Design (CRD) with five replications. Among the germplasms the maximum number of flowers (32.5/plant), the maximum number of fruits (28.8/plant), the highest average fruit weight (12.3 g) and the highest total fruit yield (361 g/plant) were found in V1. Considering the overall results of the study, it may be concluded that V1 (SAU Line-01) is a promising strawberry germplasm for cultivation in Bangladesh. DOI: http://dx.doi.org/10.3329/agric.v11i2.17495 The Agriculturists 2013; 11(2) 104-108